Development Guidelines for Training Responsibilities Learning Through The Conseling of Realities - Dewi Yulianti; I Dewa Putu Partha (Simposium Antar Bangsa Seminar dan Workshop)
Responsibility does not just appear, but is planted and forged by the environment to shape it into a habit. The fact is that at home and abroad the level of student responsibility is still low, especially at the vocational level. To increase the responsibility of learning various efforts have been made, but the results are not as expected. The responsibility of learning becomes an important issue for the attention of the stakeholders. Teacher guidance and counseling is one of the strategic functions that can help students to improve learning responsibilities. Through counseling reality groups are considered capable of increasing learning responsibility. The purpose of reality group counseling is to make individuals responsible, act according to reality, and not violate the rules or norms that apply. The reality group counseling guide is expected to help teachers of Vocational High School 3 Vocational School counseling and counseling in order to be more skillful and train the ability to carry out reality group counseling services.The research and development method in this study uses the Borg and Gall model with ten steps in the study. Ten steps are modified according to existing needs and conditions to: (1) preliminary study, (2) planning, (3) initial product development, (4) expert testing, (5) stage product revision. The test data analysis techniques for experts using Interater agreement The instrument used in this study was an assessment questionnaire and unstructured interview guidelines. While the analysis of user data (guidance counseling teachers) used descriptive statistical analysis.The test results showed that the product was suitable for use by the Vocational School 3 Malang Middle School guidance and counseling teachers to improve student learning responsibilities. Suggestion of utilization by guidance and counseling teacher of State Vocational High School 3 Malang for improving student's learning responsibility. For the next researcher, it is expected to carry out further development related to the product guidelines that have been developed.